The impact of tourism development on the economic, cultural and environmental aspects of local communities - Pratama, I Gede Surya; Mandaasari, I. A. Cynthia Saisaria (International research journal of management, IT and social sciences, 2020)
The growing development of tourism in Canggu Village encourages researchers to analyze the Impact of Tourism Development on Economic, Cultural and Environmental Aspects of the Local Community of Canggu Village in Badung Regency. The population in this study is the local community of Canggu Village which is divided into 7 banjar adat (community). The sampling method that I used was random sampling where 30 questionnaires were distributed in each banjar adat so that a total of 210 respondents were obtained. The data analysis technique that the researchers used was Path Analysis. The results show that: (1) the variable of tourism development has a significant positive effect on economic variables; (2) the variable of tourism development has a significant positive effect on cultural variables; (3) the variable of tourism development has a significant positive effect on environmental variables.